Paradise and Politics in the Music of Blind Willie Johnson (Altre Modernità, 2012)
I investigate the politics of paradises in the 1920s African-American gospel blues of Blind Willie Johnson. His recordings are apocalyptic vignettes which juxtapose and conflate paradises, using many different voices. I describe the theological and political paradises in Johnson’s songs: the Old Testament journey to Canaan; the post-death heaven in the New Testament; Christ’s kingdom on earth in Revelation; freedom in Northern cities or Canada; and a utopian dream of political emancipation of African-Americans and transformation of society in the South. I outline the various voices present in Johnson’s recordings: vocal styles; accompanying singers; the guitar; grammatical, textual and lexical voices; and the silent voices of technology and time. I suggest traces of a subtle political activism in these voices and paradises, and explore uses of these voices in linking paradises, arguing that the complex transitions enhance the force of signification and frustrate attempts to finalise meanings. Many interpretations of Johnson’s recordings, however, seek to determine final meaning, and I discuss the limitations of such attempts, limitations which not only underestimate the richness of the recordings but deny Johnson any political awareness or agency. In cautioning against this kind of project, I call for a hearing open to plural interpretations, and suggest political potential not only in coded messages, but in radical indeterminacy itself.